Knowledge Assessment among the Fourth and Fifth Year Students on the Potentially Malignant Lesions of Oral Cavity - Hadžić Sanja; Gojkov-Vukelić Mirjana; Pašić Enes; Muharemović Arma; Jahić Indira Mujić (Balkan Stomatological Society, 2020)
Background/Aim: Potentially malignant oral lesions (PMOL) are lesions that have an increased risk of malignant transformation concerning healthy oral mucosa. This research aimed to assess the knowledge of students of final years of study on the potentially malignant lesions of the oral cavity.